Determinants of employee's acceptance of a compressed workweek scheme a case study - Sundo, Marloe B.; Fujii, Satoshi; Madlangbayan, Marish S.; Ana, Eliseo V.; Velasco, Perlie P. (2015)
The study investigated the hypothesis about the consequences of a compressed workweek (CWW), i.e. reduced traffic congestion, fewer working days, longer working duration and success of government's objectives, are all determinants in the acceptance of CWW scheme. A survey of 247 public employees at the University of the Philippines Los Baños (UPLB) was carried out after the Philippine government had implemented a CWW scheme. The results of this study suggest that four psychological factors can explain around 80% of the variance in the acceptance of the CWW scheme. Attitude toward fewer working days had the largest effect among the four factors. This study also suggests that the four psychological factors were influenced by other background variables related to personal and household attributes, travel behavior patterns and changes in travel behavior patterns upon the implementation of the CWW scheme. A change in recreational activity patterns, due to the implementation of the CWW scheme, was found to be a significant background variable for the four psychological determinants considered in this study.
Keywords: Compressed workweek; Civil service -- Attitudes